Examining the Effects of Oxygen Plasma on Physical and Dyeing Properties of Some Cellulose Fibers - (:unkn) unknown (KAUNAS UNIV TECH, 2016)
Cotton, Agava Americana and artichoke fibers were treated with plasma with oxygen gas in Diener Vacuum Plasma for 1, 3 and 5 minutes, with 40 kHz low frequency and at 0.3 mbar pressure. After the plasma treatment, fibers' weight loss %, tensile strength, elongation, fiber diameter, surface topography (SEM), colour changes, and light and washing fastness properties were investigated. A positive increase was observed for mechanical and fastness properties after 5 min plasma treatment. The effects of plasma treatments on dyeing properties of fibers were studied. Dyeing properties of plasma treated fibers were improved after 3 min. treatment. SEM results were also proved the improved physical properties and colour changes due to the rough surface structure.
Keywords: cotton; Agava Americana; artichoke fibers; oxygen plasma treatment; dye exhaustion %; mechanical properties